PERANAN PIMPINAN DALAM MENCIPTAKAN EFISIENSI DAN EFEKTIVITAS BEKERJA DARI RUMAH SELAMA PANDEMI COVID-19 PADA PT PELABUHAN INDONESIA IV (PERSERO) CABANG MAKASSAR - Shofiana Syam (Cross-border, 2020)
This study aims to determine the role of leaders in creating efficiency and effectiveness of working from home during the covid-19 pandemic at PT Pelabuhan Indonesia IV (Persero) Makassar Branch. This type of research is qualitative, which is described the results of observations and interviews through online, with the employees in the company. The study was conducted from April 10 to July 6, 2020. The results showed that the role of a leader in PT Pelabuhan Indonesia IV (Persero) Makassar Branch in creating the efficiency and effectiveness of working from home during the co-19 pandemic had carried out its role properly. This is seen from the performance of employees while working from home remains productive, although there are obstacles or obstacles in its implementation such as network disruption and for mothers who have small children. However, the work produced by employees is efficient and effective, so the work program can also be achieved annually.